2004
DOI: 10.1002/hed.10387
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 and ERBB2 expression in major and minor salivary gland mucoepidermoid carcinoma

Abstract: Median survival time was 24 months (range, 2-60 months) among the nine patients who died, whereas median follow-up time in the remaining 19 patients is 33.4 months (range, 4.7-73 months). A trend toward a reduction in MUC4 antigen expression in high-grade tumors (55% expression) compared with low-grade (91% expression) and intermediate-grade (100% expression) tumors is identified (chi square, p =.0975). Patients with tumors expressing MUC4 antigens are at reduced risk of death (hazard ratio [HR], 0.20; p =.053… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…Kernohan et al (28) reported positive immunostaining for HER2 in only 1 out of 6 cases with mucoepidermoid carcinomas. However, Weed et al (23), Cho et al (24) and Press et al (25) reported HER2 overexpression in 25, 36 and 38% of the studied cases. There may be many reasons for the observed differences, including patient selection, methodology of the immunohistochemical procedures, scoring and the definition of HER2 expression.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Kernohan et al (28) reported positive immunostaining for HER2 in only 1 out of 6 cases with mucoepidermoid carcinomas. However, Weed et al (23), Cho et al (24) and Press et al (25) reported HER2 overexpression in 25, 36 and 38% of the studied cases. There may be many reasons for the observed differences, including patient selection, methodology of the immunohistochemical procedures, scoring and the definition of HER2 expression.…”
Section: Discussionmentioning
confidence: 86%
“…HER2 overexpression occurs in 0 to 38% of mucoepidermoid carcinoma (22)(23)(24)(25)(26)(27)(28). So far, no previous study has evaluated the EGFR and HER2 expression in metastases and compared such an expression with that of corresponding primary mucoepidermoid carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MUC4 expression is related to aggressive tumor behavior or a poor outcome in intrahepatic cholangiocarcinoma, invasive ductal carcinoma of the pancreas, extrahepatic bile duct carcinoma, and lung adenocarcinoma (13)(14)(15)(16)(17). On the other hand, loss of MUC4 expression is related to poor survival in mucoepidermoid carcinoma of the salivary gland, squamous cell carcinoma of the upper aerodigestive system, and adenocarcinoma of lung (18)(19)(20)(21). The function of MUC4 in gastric cancer is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…The amplification and/or overexpressiom of c-erbB-2 in human tumor tissue has been associated with a poor prognosis in ovarian, endometrial and breast carcinoma (Weed et al, 2004). Previous studies of c-erbB-2 expression in salivary gland carcinomas are sparse, comprise heterogeneous subtypes, and show contradictory results (Locati et al, 2005).…”
Section: Introductionmentioning
confidence: 99%